Integration of a nanostructured dielectrophoretic device and a surface-enhanced Raman probe for highly sensitive rapid bacteria detection1. Issue 8 (28th February 2015) - Madiyar, Foram Ranjeet; Bhana, Saheel; Swisher, Luxi Z.; Culbertson, Christopher T.; Huang, Xiaohua; Li, Jun
<x xml:space="preserve">Abstract</x> This work reports a synergistic approach to the concentration, detection and kinetic monitoring of pathogens through the integration of nanostructured dielectrophoresis (DEP) with nanotag-labelled Surface Enhanced Raman Spectroscopy (SERS).